Rhetorical functions of silence among speakers of some Nigerian languages: cultural and individual perspectives - Ibrahim, Bashir; Abdullah, Ain Nadzimah; Rafik - Galea, Shameem; Mohd Kasim, Zalina (American Research Institute for Policy Development, 2017)
Recently, there has been renewed interest in the study of silence as a linguistic tool used by humans for communication purposes. Since the work of Nwoye (1985) on eloquent silence among the Igbo of Nigeria, little study has been conducted on the use of silence among other myriad Nigerian tribes. Yet, there has been a general claim that Africans use silence in formal and social situations more frequently than their European and North American counterparts. This study seeks to understand and explain rhetorical functions of silence among speakers of some Nigerian languages. Focus group discussions were held to elicit data from some undergraduate students of two public universities in Northern Nigeria involving speakers of Hausa/Fulani, Igala, Yoruba, Idoma, Igbo, Tiv,Meroeh, Lunguda, and Nupe. Two discussions were held with 300 level students of the Department of English, 400 level students of the Department of Physics and 300 level students of the Department of Biological Sciences. The discussion lasted about twenty minutes with each of the group.The results indicated that silence in conversation performs at both illocutionary and perlocutionary levels, having both negative and positive connotations depending on the context, situation, and the participants involved. The findings indicated that silence is ubiquitous in human communication repertoire, irrespective of culture. Intra-and intercultural variation, however, exist on the perception of various cultures around the world on the use of silence in conversation.